Is this the Asian century? - Lee, Jong-Wha 1960- (New Jersey World Scientific, 2018)
"Comprises 25 articles which the author has published on the Project Syndicate website since 2012. These articles are grouped into four broad topics: (1) Growth and Structural Adjustment, (2) Economic Integration and Cooperation, (3) Business, Money, and Finance, and (4) Education and Society. Through these selected works, the author explores whether the Asian Century is coming to pass or not and how Asian economies prepare for such century. The author also presents his analyses of Asia's economic transformation as well as social and cultural changes, and suggests the ways that Asian economies can overcome major economic and social challenges to continue their path towards a more balanced and sustainable growth in the 21st century. This book serves as a useful reference text for those who seek to understand the Asian economies, and contributes to ongoing policy debate on Asia's economic future".
Includes bibliographical references and index.
Keywords: Asia -- Economic conditions -- 21st century; Asia -- Economic policy